IT-driven patient safety at the heart of radiology service improvement. - Moores, Michael (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Patient safety is a fundamental requirement of modern health-care systems and the application of information technology (IT) to this activity should have improvements in the area as one of its goals. Indeed, ensuring that the diagnostic IT strategy is optimized, for example, the use of IT in service redesign or data analysis, forms one of the main platforms for the National Framework for Service Improvement in Radiology. This paper presents both the concept behind and the results of a project that has been under way in the UK involving St. Helens and Knowsley NHS Trust and IRS Ltd concerned with implementing effective IT-driven scientific support in the field of medical radiation protection. Locally developed software is employed in assessing, managing and analysing patient dose data arising from X-ray examinations performed in the busy department of a large district general hospital (DGH). Such data are analysed in a variety of ways, for example, over time and according to location (department or X-ray room). This analysis not only provides a measure of performance against nationally agreed dose reference levels (DRLs) but also enables a detailed analysis of any variations as well as the establishment of local DRLs (performance indicators). This process provides quantitative input to management strategies aimed at service improvement. Such strategies are geared towards the support of the Ionizing Radiations (Medical Exposures) Regulations 2000 as well as implementation of quality-management principles at the heart of radiology practices.